Indoor Air Auality (IAQ) characteristics and microbial identific ations in two selected schools in Pahang, Malaysia - Arifin, Mohd Hizrri; Mohd Ghazi, Zati Nabilah; Zaidi, Nurul Amni; Mohd Nazri, Nur Shahidah; Zahaba, Maryam; Abdul Hadi, Hazrin; Sharif, Mohd Faez; Mohd Aris, Mohd Shukri (2016)
It is important to assess IAQ characteristics and to identify possible microbial contaminants in schools indoor environment because children are more vulnerable to air pollutants as they inhale more air pollutants per kilograms of body weight. Objectives: This study is done to assess and to compare the level of selected IAQ parameters and microbiological contaminants inside the classroom of schools in urban area and rural area during occupied and non-occupied period. This study also aims to identify airborne bacteria species and fungi genera within classroom of schools in those area. Methods: School X (SX) is located in Kuantan, Pahang, while school Y (SY) is located in Pekan, Pahang. The physical IAQ parameters (Temperature, Relative Humidity (RH), Carbon Dioxide (CO2)) and airborne particulate matter (PM) were measured using VelociCalc® Multi-Function Ventilation Meter 9565 (TSI®, Minnesota, USA), and DustMate (Turnkey Instruments, UK) respectively. Surface Air System Indoor Air Quality (SAS IAQ), (PBI International, Italy) was used to collect the microbial contaminants and subsequently CFU were counted. The data were recorded for 30 minutes for each time-slot for 8 hours during occupied and non-occupied period within selected classrooms. Bacteria identification was done using 16S rRNA gene sequence analysis and fungi were identified macroscopically through direct identification technique up to genus level. The results were compared to standard reference limit based on Industrial Code of Practice on Indoor Air Quality (ICOP, 2010) regulated by the Department of Occupational Safety and Health (DOSH, 2005). Results: This study found that temperature (SX, Occupied; 34.9±3.9, Non-Occupied; 32.8±0.7), (SY, Occupied; 30.7±0.2, Non-Occupied; 30.6±0.5), RH (SY, Occupied; 74.4±2.9, Non-Ocupied; 70.05±1.0) and bacterial CFU counts (SX, Occupied; 558±308), (SY; Occupied; 903±415, Non-Occupied; 1176±303) exceeded the standard limit regulated by DOSH. Number of gram-negative bacteria dominated over gram-positive bacteria in both settings. Bacillus sp. (B. atrophaeus, B. subtilis, B. pumilus, B. altitudinis,. B. tequilensis and B. aerophilus). were the most dominant species, followed by Staphylococcus sp. (S. warneri, S. sciuri, S. haemolyticus and S. gallinarum). The common fungal species isolated in both schools during occupied and non-occupied period were Aspergillus, Alternaria, Cladosporium, Penicillium and Mucor.